Wound fluid from breast cancer patients undergoing intraoperative radiotherapy exhibits an altered cytokine profile and impairs mesenchymal stromal cell function - Wuhrer, Anne; Uhlig, Stefanie; Tuschy, Benjamin; Berlit, Sebastian; Sperk, Elena; Bieback, Karen; Sütterlin, Marc (Cancers, 2021)
Simple Summary - Intraoperative radiotherapy (IORT) is increasingly used in the therapy of early breast cancer. Besides the direct radiotoxic effects, IORT may add at inhibiting local recurrences by a modulation of the microenvironment. Our aim was to assess the impact of IORT in altering immunological responses and wound healing processes. Thus, we analyzed surgical wound fluid collected after breast conserving surgery with and without IORT concerning acute changes in immune cell populations and cytokine levels. Furthermore, their impact on functions of breast cancer cells and mammary mesenchymal stromal cells (MSC) was assessed. We found no changes in the immune cell composition, yet group-related differences in the expression levels of several cytokines. The application of the wound fluid in MSC cultures caused group-dependent differences in MSC proliferation, wound healing and migration with an alteration of the MSC secretome. Our findings help to elucidate the biological effects of IORT and to clarify the concomitant role of MSC. - - Abstract - Intraoperative radiotherapy (IORT) displays an increasingly used treatment option for early breast cancer. It exhibits non-inferiority concerning the risk of recurrence compared to conventional external irradiation (EBRT) in suitable patients with early breast cancer. Since most relapses occur in direct proximity of the former tumor site, the reduction of the risk of local recurrence effected by radiotherapy might partially be due to an alteration of the irradiated tumor bed’s micromilieu. Our aim was to investigate if IORT affects the local micromilieu, especially immune cells with concomitant cytokine profile, and if it has an impact on growth conditions for breast cancer cells as well as mammary mesenchymal stromal cells (MSC), the latter considered as a model of the tumor bed stroma.42 breast cancer patients with breast-conserving surgery were included, of whom 21 received IORT (IORT group) and 21 underwent surgery without IORT (control group). Drainage wound fluid (WF) was collected from both groups 24 h after surgery for flow cytometric analysis of immune cell subset counts and potential apoptosis and for multiplex cytokine analyses (cytokine array and ELISA). It served further as a supplement in cultures of MDA-MB 231 breast cancer cells and mammary MSC for functional analyses, including proliferation, wound healing and migration. Furthermore, the cytokine profile within conditioned media from WF-treated MSC cultures was assessed. Flow cytometric analysis showed no group-related changes of cell count, activation state and apoptosis rates of myeloid, lymphoid leucocytes and regulatory T cells in the WF. Multiplex cytokine analysis of the WF revealed group-related differences in the expression levels of several cytokines, e.g., oncostatin-M, leptin and IL-1β. The application of WF in MDA-MB 231 cultures did not show a group-related difference in proliferation, wound healing and chemotactic migration. However, WF from IORT-treated patients significantly inhibited mammary MSC proliferation, wound healing and migration compared to WF from the control group. The conditioned media collected from WF-treated MSC-cultures also exhibited altered concentrations of VEGF, RANTES and GROα. IORT causes significant changes in the cytokine profile and MSC growth behavior. These changes in the tumor bed could potentially contribute to the beneficial oncological outcome entailed by this technique. The consideration whether this alteration also affects MSC interaction with other stroma components presents a promising gateway for future investigations.